(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pyridoxine hydrochloride, known as vitamin B6, plays a key role in the human body by participating in amino acid metabolism, neurotransmitter synthesis, and maintaining the normal functioning of the central nervous system. Quantitative evaluation of pyridoxine in vivo is necessary to assess its level in the body, diagnose deficiency and monitor therapeutic use. The quantitative determination of pyridoxine hydrochloride in vivo is an important area of pharmacokinetic research, since vitamin B6 plays an important role in maintaining metabolism, neurotransmitter synthesis and the normal functioning of the nervous system. Various analytical methods such as high-performance liquid chromatography (HPLC) and mass spectrometry are used to assess its content in the body.